Monitoramento espacial e temporal de parâmetros físico-químicos da água no rio Alegria, Medianeira-PR - Cecchin, Josimara (2017)
The determination of the water quality of a hydric body is very important, considering its role to the population’s supply and ecosystem maintenance. Usually, the assessment happens through physical and chemical parameters. This study aims to establish a relationship between these space and time variables and the situation of Alegria River in the city of Medianeira, state of Paraná. This choice considered the fact that the river is a water source, which crosses an urban area and it is subject to several environmental impacts throughout its course. Two campaigns were carried out during 2017’s winter and spring in four points located between the river’s springhead and mouth, to detect possible space changes in its characteristics. The investigated parameters were pH, alkalinity, hardness and chloride; oxygen dissolved, fluoride, chemical demand of oxygen, nitrite, nitrate ammonia nitrogen and total phosphor. The results indicated the third point sample as the most critical one, which allowed this study to infer that there is an influence of anthropic sources on the water quality. This happens because of launching of domestic sewage and agro industrial effluents into the river. However, the launching is not representative yet to cause meaningful hazardous environmental impacts to the hydric body and to human beings, since the only parameters in disagreement with the CONAMA Resolution 357/05 were the ammonia nitrogen and the phosphor in two stations. Alegria River has shown it is able to carry out a self-purification process satisfactorily, which lowers its pollution indexes until it reaches its mouth.